Cidade, segregação e comida: estudo do ambiente alimentar no contexto de desigualdade socioespacial de Petrópolis (Rio de Janeiro, Brasil) - Emanuela Alves da Rocha; Patricia Regina Chaves Drach; Eloisa Carvalho de Araujo (Cidades, Comunidades e Território)
The food landscape of Brazilian cities is directly linked to territorial planning and socio-spatial inequality. This article characterizes the agro-food environment in the first district of Petrópolis (Rio de Janeiro, Brazil) and analyzes more sustainable alternatives that strengthen short consumption circuits. The mapping of food-related commercial and agricultural establishments is part of this study. The analysis, combined with the average family income by census sector, the division by neighborhoods, and certain characteristics of urban mobility, allows for reflection on priority areas for action and forms of investment, through public policies, in the direct relationship between producer and consumer, such as the expansion of street markets, and the creation of structures for direct sale along public spaces. Food segregation as a reality in Petrópolis and the recognition of the importance of the rural environment and local production must be considered to identify more sustainable solutions to mitigate food insecurity.